PENGUATAN KAPASITAS PROMOSI DIGITAL PADA KELOMPOK UMKM DI KABUPATEN BUTON SELATAN - Pardana, Deki; Zamha Zamihu, Juamdan; Jasiyah, Rabiyatul (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
This community service aims to strengthen the capacity of digital promotion in Micro, Small and Medium Enterprises (MSMEs) groups in South Buton Regency through a qualitative approach. The method of this activity was carried out by organising a seminar attended by MSME players in the region. The seminar was designed to provide an in-depth understanding of digital promotion strategies and the effective use of digital technology to increase the competitiveness and market reach of MSMEs. The results of the activity showed that the active participation of participants in the seminar was able to increase their digital knowledge and skills, thus enabling the implementation of more effective promotional strategies In addition, the findings underscore the importance of ongoing support and intensive training to ensure the implementation and sustainability of digital promotion strategies among MSME actors. In conclusion, strengthening digital promotion capacity can be a key factor in driving local economic growth and competitiveness of MSMEs in South Buton District.